Comparative Study of Distribution of Active Sites According to Their Stereospecificity in Propylene Polymerization over the Traditional TiCl3 and Supported Titanium–Magnesium Catalysts with Different Composition. Issue 5 (15th January 2018) - Nikolaeva, Marina; Matsko, Mikhail; Zakharov, Vladimir
Abstract: The preparative‐temperature rising elution fractionation method is used to obtain comparative data on contents of fractions with different microtacticities for polypropylene (PP) samples prepared using three catalytic systems: the traditional Ziegler–Natta (Z–N) catalyst δ‐TiCl3 and two types of supported titanium–magnesium catalysts: the "donor‐free" TiCl4 /MgCl2 catalyst and TiCl4 /MgCl2 · n DBP catalyst (DBP – dibutylphthalate used as an internal donor) at polymerization with the same cocatalyst (AlEt3 ) in the absence and presence of an external donor (propyltrimetoxy silane). The separated individual PP fractions are also studied by gel permeation chromatography (molecular weight and molecular weight distribution) and differential scanning calorimetry. The results demonstrate general regularities and differences in the formation of active sites having different isospecificities for the traditional TiCl3 ‐based Z–N catalyst and highly active supported titanium–magnesium catalysts. Abstract : Data on the distribution of fractions with different isotacticity are compared for polypropylene samples produced over catalysts that belong to three generation of Ziegler‐Natta catalysts: δ‐TiCl3, "donor‐free" titanium–magnesium catalyst (TMC), and TMC containing an internal donor (dibutyl phthalate) upon polymerization with the same cocatalyst (AlEt3 ) in the absence and presence of an external donor.